Efektivitas SPA Kaki (Foot SPA) Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif - Sjenny Olga Tuju; Getruida B. H. Alow; Ike Utamasari; Atik Purwandari (POLTEKKES KEMENKES MANADO, 2022)
Background: Labor pain is uterine contraction that perceived as a pain on back, abdominal and spread along to thigh area. Pain can be treated with pharmacological and non pharmacological method. Pharmacological method by giving drugs and non pharmacological method with scientific method such as foot SPA.. Objective: To understand the effectiveness of Foot SPA on pain intensity of active phase of 1st stage Labor Method: This is a quassi-experimental study with one group pre and posttest design which done to 15 samples, data was collected with observational form filled by researcher by doing an interview to respondent before and after getting Foot SPA. Data was analyzed with Wilcoxon Signed rank Test. Result: This study shows that on average the respondent’s pain intensity before get Foot SPA was 6.87 and decrease to 4.27 after getting Foot SPA. Analyzed data shows the p-value < 0.05 Conclusion: Foot SPA effective to decrease pain intensity of 1st stage active phase labor at Tuminting Public Health Center Manado. We advising Foot SPA to be a standardized health services as a new approach in labor pain management.